Development of Project-Based University Student Work Sheets in Student's Kitchen Management Course - Nuwairi Hilda; Ana Rahmi; Ismail Jahidin; Dina Ampera; Siti Wahidah (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to produce a Project-based Team-based student worksheet in the Kitchen Management course. This type of research is research and development that refers to model development, with stages (1) self-evaluation stage consisting of analysis and design (2) prototyping stage consisting of expert review, one to one and small group (3) field test stage . The data were collected using quantitative descriptive analysis techniques through questionnaires or questionnaires related to the quality of product development. The results showed that student learning outcomes were seen from the pre-test, post-test and mid-semester exams in the course Evaluation of Kitchen Management Learning Outcomes. Catering Education students experienced a significant increase after using this project-based student worksheet.